Math, asked by kahnu135, 1 year ago

(a2-b2)(a2+b2)-(a2-b2)2

Answers

Answered by Anonymous
5

➖➖➖➖➖➖➖

ANSWER

⬇️⬇️⬇️⬇️⬇️⬇️⬇️

=>

( {a}^{2}  -  {b}^{2} )( {a}^{2} +  {b}^{2}  ) -{ ( {a}^{2}  -  {b}^{2}) }^{2}

=>

 {( {a}^{2} -  {b}^{2} ) }^{2}  -  {( {a}^{2} -  {b}^{2} ) }^{2}

=>

0

⬆️ ⬆️ ⬆️ ⬆️ ⬆️ ⬆️

HOPE YOU GOT IT

➖➖➖➖➖➖➖


Anonymous: .. loved to help you .. thanks
kingArsh07: hi
Answered by siyamittal595
9

(a²-b²)(a²+b²)-(a²-b²)²

=(a^4-b^4)-(a^4+b^4-2a²b²)

=a^4-b^4-a^4-b^4+2a²b²

=-2b^4+2a²b²

Similar questions